Advanced Maternal Age in IVF: Still a Challenge? The Present and the Future of Its Treatment - Ubaldi, Filippo Maria; Cimadomo, Danilo; Vaiarelli, Alberto; Fabozzi, Gemma; Venturella, Roberta; Maggiulli, Roberta; Mazzilli, Rossella; Ferrero, Susanna; Palagiano, Antonio; Rienzi, Laura (Frontiers in Endocrinology, 2019)
Advanced maternal age (AMA; >35yr) is associated with a decline in both ovarian reserve and oocyte competence. At present, no remedies are available to counteract the aging-related fertility decay, however different therapeutic approaches can be offered to women older than 35yr undergoing IVF. This review summarizes the main current strategies proposed for the treatment of AMA: i) oocyte cryopreservation to conduct fertility preservation for medical reasons or “social freezing” for non-medical reasons, ii) personalized controlled ovarian stimulation to maximize the exploitation of the ovarian reserve in each patient, iii) enhancement of embryo selection via blastocyst-stage preimplantation genetic testing for aneuploidies and frozen single embryo transfer, or iv) oocyte donation in case of minimal/null residual chance of pregnancy. Future strategies and tools are in the pipeline that might minimize the risks of AMA through non-invasive approaches for embryo selection (e.g. molecular analyses of leftover products of IVF, such as spent culture media). These are yet challenging but potentially ground-breaking perspectives promising a lower clinical workload with a higher cost-effectiveness. We also reviewed emerging experimental therapeutic approaches to attempt at restoring maternal reproductive potential, e.g. spindle-chromosomal complex, pronuclear or mitochondrial transfer, and chromosome therapy. In vitro generation of gametes is also an intriguing challenge for the future. Lastly, since infertility is a social issue, social campaigns and education among future generations are desirable to promote the awareness of the impact of age and lifestyle habits upon fertility. This should be a duty of the clinical operators in this field.